Antimicrobial activity of a new nanobased endodontic irrigation solution: In vitro study - Leila Moghadas; Mahdi Shahmoradi; Tahmineh Narimani (Wolters Kluwer Medknow Publications, 2012)
Aims: The purpose of this study was to introduce a nanosilver particle based endodontic irrigation solution and to evaluate its antimicrobial efficacy in comparison to 5.25% NaOCl. Materials and Methods: In an in vitro experiment the effect of the new irrigant against Enterococcus faecalis (ATCC: 29212) and Staphylococcus aureus (ATCC 25923), two most commonly isolated species of root canal space, was studied in different time intervals of 3, 5 and 15 minutes. Results: No growth of E. faecalis and S. aureus was observed in any of irrigant groups and any of different time intervals. Conclusion: These results indicate that the new irrigant is as effective as NaOCl in preventing the bacterial growth of common root canal bacteria.